Cracking Controls ATP Hydrolysis in the catalytic unit of a P-type ATPase - Placenti, M.Agueda; Martinez-Gache, Santiago A.; González-Lebrero, Rodolfo M.; Wolynes, Peter G.; González Flecha, F.Luis; Roman, Ernesto A. (Journal of molecular biology, 2025)
[Display omitted] •The isolated AfCopA-NP catalytic unit conserves its optimal working temperature and apparent affinity for ATP.•Small additions of urea increase ATPase activity.•A characterization of the native conformational ensemble was performed by a combination of local frustration and AlphaFold2 analysis.•A detailed kinetic model is proposed to account the effects of urea, temperature and ATP.•Our results suggest a cracking-like mechanism in the modulation of the ATPase activity. Membrane transporters are essential for homeostasis and among them P-type ATPases are key players. Despite extensive research, conformational changes in their catalytic unit and their coupling to ATP hydrolysis are not explored in detail. In this work, we analyzed the effect of ATP, temperature, and urea on the steady-state ATPase activity, tryptophan fluorescence and far-UV ellipticity of the catalytic unit of the thermophilic Cu(I) transport P1B-ATPase from Archaeoglobus fulgidus. Combining local frustration analysis with AlphaFold2 structure prediction, we identified an open conformation which we used to perform structure-based model simulations of the open-closed transition. We developed a mechanistic model that fully describes all of our experimental observations. Our results revealed a “cracking”-like mechanism involved in the catalysis of ATP hydrolysis. These findings reinforce that, although simple, the isolated catalytic unit is a relevant model to study the role of local unfolding in the catalytic mechanism of these proteins.